Linking ESG-Driven portfolios to financial inclusion outcomes: An econometric investigation of fintech-enabled sustainable investing - Poonam, Poonam; Santosh, Indu; Prakash, V; Maurya, Mohit Kumar; Dilip, R (The International tax journal, 2026)
This paper explores the empirical relationship between investment portfolios driven by ESG and the financial inclusion outcomes with particular emphasis on the enabling provisions of FinTech on sustainable investing. Although ESG investing has become prominent in the world, there is little evidence of its capacity to produce quantifiable inclusion results. The study utilizes both direct and indirect effects with the help of a multi-country panel dataset during a decade timeframe, utilizing fixed-effects, interaction models, dynamic panel GMM, and mediation analysis. The findings indicate that ESG portfolio is positively and statistically relevant in financial inclusion where a one percentage point increase in ESG allocation brings about an average increase in financial inclusion index of 0.34 percentage points. The adoption of FinTech, in its turn, positively influences inclusion (0.30), whilst its impact on ESG is greater, which is illustrated by the positive ESG x FinTech interaction (0.16, p < 0.01). Dynamic GMM estimates confirm the robustness of the results and the ESG coefficients are not negligible (significant 0.26) when endogeneity and persistence effects are taken into consideration. Further results of mediation indicate that about 37 percent of the overall impact of ESG on financial inclusion is relayed by the adoption of FinTech.